ACCOUNTING TREATMENT OF CRYPTO ASSETS: : A THEORETICAL APPROACH - Rodríguez, Francisco (Revista Arbitrada Formación Gerencial, 2024)
The fundamental objective of this article is to develop theoretical knowledge for the use and understanding of cryptoassets, as well as the development of skills and competencies to identify, measure, record, present and reveal transactions with cryptoassets according to established criteria. The research is bibliographic documentary type according to Arias (2006). It is concluded that since there is no specific standard for the accounting recognition of digital assets, the International Accounting Standards Board (IASB) through the International Financial Reporting Standards Interpretations Committee (IFRIC) has issued criteria on: what should be the accounting recognition to be given to these assets. In this sense, Spain, Mexico and Venezuela have developed a local regulatory framework.